2017
DOI: 10.1111/imm.12835
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of γδ T‐cell activation by neutrophil elastase

Abstract: γδ T cells are non-conventional, innate-like T cells, characterized by a restricted T-cell receptor repertoire. They participate in protective immunity responses against extracellular and intracellular pathogens, tumour surveillance, modulation of innate and adaptive immune responses, tissue healing, epithelial cell maintenance and regulation of physiological organ function. In this study, we investigated the role of neutrophils during the activation of human blood γδ T cells through CD3 molecules. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“… 121 Interestingly, using phosphoantigen HMBPP rather than ZOL (used in our studies), Towstyka et al observed that neutrophils and elastase actually costimulated IFN-γ production in anti-CD3 activated γδ T cells rather than exerting inhibitory effects. 122 This apparent discrepancy illustrates the complexity of the relationship between neutrophils and γδ T cells, as different modes of activation of γδ T cells were applied: the indirect activation with ZOL used by us 119 induced a neutrophil burst, which was not the case using direct stimulation of γδ T cells with pAg HMBPP 121 or BrHPP (used by us as a control 119 ). Further analyzing the regulatory interactions between neutrophils, tumor cells and γδ T cells in vitro, we also observed contrasting effects of neutrophils, depending on situational factors and the activation status of cells.…”
Section: γδ T Cells: Regulating and Being Regulatedmentioning
confidence: 99%
“… 121 Interestingly, using phosphoantigen HMBPP rather than ZOL (used in our studies), Towstyka et al observed that neutrophils and elastase actually costimulated IFN-γ production in anti-CD3 activated γδ T cells rather than exerting inhibitory effects. 122 This apparent discrepancy illustrates the complexity of the relationship between neutrophils and γδ T cells, as different modes of activation of γδ T cells were applied: the indirect activation with ZOL used by us 119 induced a neutrophil burst, which was not the case using direct stimulation of γδ T cells with pAg HMBPP 121 or BrHPP (used by us as a control 119 ). Further analyzing the regulatory interactions between neutrophils, tumor cells and γδ T cells in vitro, we also observed contrasting effects of neutrophils, depending on situational factors and the activation status of cells.…”
Section: γδ T Cells: Regulating and Being Regulatedmentioning
confidence: 99%
“…Controversial observations have been reported on the crosstalk occurring between neutrophils and γδ T cells in both humans and mice . Human neutrophils were shown to either stimulate γδ T cells, or negatively modulate γδ T‐cell activation, mostly through the release of serine proteases or ROS production. Recently, immunosuppressive LDNs/PMN‐MDSCs were shown to suppress γδ T‐cell function .…”
Section: Neutrophils and T Cellsmentioning
confidence: 99%
“…The neutrophil has been shown to regulate ɣδTc. Two neutrophil-derived products, neutrophil elastase (NE) and reactive oxygen species (ROS) have been found to exert opposing effects on ɣδTc; activating the T-cells with NE and inhibiting with ROS 110 . Both of these factors have been found in the gingival crevice and shown to be stimulated by oral bacteria 111 , 112 .…”
Section: Immune Landscape Of the Oral Mucosamentioning
confidence: 99%
“…Repeated exposure of P. gingivalis LPS tolerized monocytes which then significantly increased ROS production in neutrophils and inhibited neutrophil chemotaxis 161 . While ROS has been found to inhibit γδTc activity 110 , nitric oxide (NO) has been shown to protect γδTc from apoptosis 162 . P. gingivalis LPS can elicit the production of NO in vivo 163 with a subsequent study showing the involvement of TLR9 164 .…”
Section: Oral Microbiome: Naturally Derived Adjuvantsmentioning
confidence: 99%